1998
DOI: 10.1053/euhj.1997.0854
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary sodium intake on left ventricular diastolic filling in early essential hypertension

Abstract: Aims Dietary sodium intake modulates left ventricular hypertrophy in established essential hypertension independent of blood pressure level. We conducted this study to elucidate the relationship between sodium intake and left ventricular structural or functional changes in early essential hypertension.Methods Forty-four young male patients (age 25·9 ± 2·6 years) with mild essential hypertension that had never been treated and 45 normotensive male control subjects of similar age were examined. Dietary sodium in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 0 publications
0
17
1
Order By: Relevance
“…The presence of impaired systolic function would blunt BP rise, 9 whereas diastolic dysfunction may be associated with an exaggerated BP rise during exercise, 19 but with more advanced degree of diastolic dysfunction, the cardiac stroke volume during exercise fails to increase adequately and this limits BP rise. 9 As aldosterone impairs vascular endothelial function, 14 it would not be surprising that it would also cause left ventricular diastolic dysfunction where there is an excess aldosterone activity, 20 which may interact adversely with dietary salt 21 in producing this functional cardiac abnormality. The key to understanding the pathogenesis of hypertension may be to unravel the mechanism(s) behind this inappropriate aldosterone secretion as represented by a raised ARR.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of impaired systolic function would blunt BP rise, 9 whereas diastolic dysfunction may be associated with an exaggerated BP rise during exercise, 19 but with more advanced degree of diastolic dysfunction, the cardiac stroke volume during exercise fails to increase adequately and this limits BP rise. 9 As aldosterone impairs vascular endothelial function, 14 it would not be surprising that it would also cause left ventricular diastolic dysfunction where there is an excess aldosterone activity, 20 which may interact adversely with dietary salt 21 in producing this functional cardiac abnormality. The key to understanding the pathogenesis of hypertension may be to unravel the mechanism(s) behind this inappropriate aldosterone secretion as represented by a raised ARR.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, by design, included only individuals who met specific BP criteria (12,24,28,37,65,67,79,84,92). Other studies performed stratified analyses based on BP cut-off points (54,55).…”
Section: Ci: Confidence Intervalmentioning
confidence: 99%
“…Initially evaluated to examine the relationship with BP, these analyses revisit the National Health and Nutrition Examination Survey (NHANES) data (44,45) and intervention studies, such as the Trials of Hypertension Prevention (TOHP) Phase I (TOHP I) and Phase II (TOHP II) (21) and the Trial of Nonpharmacological Interventions in the Elderly (TONE) (8). This review encompasses 17 observational studies that address the association between sodium intake and CVD (37,44,45,52,68,(84)(85)(86)(87), including measures of cardiac dysfunction (12,24,28,29,54,55,67,79). Although there are currently no randomized clinical trials of CVD morbidity and mortality in relation to sodium intake, two intervention studies evaluate sodium's effects on the vasculature (36,80), three studies evaluate sodium and measures of cardiac dysfunction (34,51,90), and four studies explore longitudinal outcomes for individuals having taken part in an intervention study (8,21,65,92,94).…”
Section: Introductionmentioning
confidence: 99%
“…In their pioneering study of a Chinese population, Avolio et al [15] demonstrated that increased consumption of salt (13.3 g NaCl/day vs. 7.3 g NaCl/day) was associated with significantly higher stiffness of the aortal wall measured using the pulse wave velocity method, regardless of the age and BP of the subjects. Other authors have also demonstrated a BP-independent influence of sodium on left ventricular hypertrophy [16] and impaired contractility of the left ventricle [17].…”
Section: The Role Of Sodium In the Pathogenesis Of Hypertensionmentioning
confidence: 88%